Georgiou, A. M. (2016, December). Applications of TMS to therapy of Aphasia after Stroke. Oral Presentation at the 2 nd Meeting of Melathron Agoniston EOKA and the Department of Rehabilitation Sciences of the Faculty of Health Sciences of Cyprus University of Technology, Limassol, Cyprus. Contemporary Methods of Neurological Rehabilitation, Limassol, Cyprus. - Georgiou, Anastasios M. (My University, 2026)
Georgiou, A. M. (2016, December). Applications of TMS to therapy of Aphasia after Stroke. Oral Presentation at the 2 nd Meeting of Melathron Agoniston EOKA and the Department of Rehabilitation Sciences of the Faculty of Health Sciences of Cyprus University of Technology, Limassol, Cyprus. Contemporary Methods of Neurological Rehabilitation, Limassol, Cyprus.